Alternative models of transition and institutional development. (1st December 2005) - Marangos, John
Alternative models of transition are associated with alternative institutional development processes. Alternative models of transition are based on different methods of economic analysis, political structures, views of 'what is a good society?' and the speed of implementing the transition policies. As a result, five alternative models of transition are considered: the Shock Therapy model of transition, the Neoclassical Gradualist model of transition, the Post Keynesian model of transition, the Pluralistic Market Socialist model of transition and the Non-Pluralistic Market Socialist model of transition (the Chinese model of transition). The most appropriate method of institutional development depended on how social reality was viewed and what was considered acceptable, desirable and feasible. It depended on assumptions about economic behaviour, the method of analysis and the goals associated with the transition process. Essentially, the choice depended on what was considered to be efficient: a market mechanism providing market-produced institutions, or state intervention providing state-produced market institutions.